PEMBUATAN KOLAM IKAN UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT DESA SIGAPITON KECAMATAN AJIBATA - Ananda Yuli Fazilah Tanjung; Welmar Olfan Basten Barat (Abdi Jurnal Publikasi, 2024)
Sigapiton is one of the villages in Ajibata District, Toba Regency, with an area of 70.80 km² (BPS,2018). Sigapiton village consst of Hamlet I (Lumban Butar-butar 1 and Lumban Butar-butar 2), Hamlet II (Sosor Dolok. Sosor Baringin, Lumban Nauli,Lumban Hasatan). Sigapiton village has a total of 175 has of families, assuming that each family has 4—7 people. Community Service Lectures (KPPM) are a from of practical learning activities in the contecxt of applying interdisciplinary knowledge which studens carry out directly in the community. The activity of making a fsh pond begins by explaining the purpose of the service, namely s that the community can use the fish pond si that they can earc income from the pond. With the availability of a pond containing tilapia fish in sigapiton cillage, it is hoped that it will be able to encourage local residents, especially Sigapiton residents who do not have permanent jobs, to be involved in raising these tilapi fish so that the community will be more prosperous. By making this pond, income will increase.